(untitled) (Journal of Computational Innovation and Analytics (JCIA), 2023)
A Real Estate Investment Trust (REIT) is a fund or trust that owns and manages commercial real estate and generates revenue. After two years of the COVID-19 pandemic, the whole REITs sector suffered from lockdown, diminishing revenue from office and shopping mall rentals. Hence, investors may lose more than expected on invested capital without further analysing this situation. This highlights the importance of investors knowing the risk of investing in REITs to plan their investment strategies appropriately. The Value at Risk (VaR) is widely employed to calculate the investment risk under a mathematical model to achieve this. A past review suggested that two approaches had been utilised for modelling, i.e., parametric and non-parametric methods. The methods under non-parametric include historical simulation, Monte Carlo simulation, and bootstrapping simulation. Thus, comparing parametric methods, historical simulation, Monte Carlo simulation, and bootstrapping simulation is essential in determining the best method to analyse the VaR in the Malaysia REITs (M-REITs) sector, which particularly focuses on Malaysia. Actual previous five-year history raw price data for each REIT in Malaysia are extracted from Yahoo Finance, Refinitiv Eikon, and DataStream via University Utara Malaysia’s (UUM) e-resources database. The result of VaR from those methods is compared and validated using backtesting. Other than that, the result reveals that the parametric method and Monte Carlo simulation are good methods for REIT’s VaR calculations in Malaysia, which are close to the current value for 12 from 17 M-REITs companies.